Utilization of Eucheuma cottonii Meal as a Functional Feed Additive for Improving Pigmentation, Health, and Growth in Ornamental Goldfish (Carrasius auratus) - Alim, Sahrul; Marzuki, Muhammad; Asri, Yuliana (Journal of Fish Health, 2025)
Color enhancement in ornamental fish is an essential quality parameter that directly influences market value and consumer preference. Natural pigments derived from marine resources, such as seaweed, offer a sustainable alternative to synthetic color enhancers. This study aimed to determine the effect of seaweed meal (Eucheuma cottonii) on the color brightness of goldfish (Carassius auratus). Goldfish used had an initial weight of 10.12 ± 0.06 g and an initial length of 5.08 ± 0.02 cm. Fish were fed using the ad libitum method three times daily with four feed treatments: P1 (Control), P2 (4 g seaweed meal), P3 (8 g seaweed meal), and P4 (12 g seaweed meal). The study was conducted for 45 days to evaluate growth performance and color characteristics. A completely randomized design with four treatments and three replications was applied. Data were analyzed using one-way ANOVA at a 95% confidence level (p < 0.05). Results showed that the addition of seaweed meal significantly influenced the red hue variable in goldfish. Brightness showed no significant difference among treatments, with the highest value in P4 (55.88%) and the lowest in P3 (52.68%). The red hue differed significantly, with the highest value in P3 (16.96%) and the lowest in P1 (9.13%). The yellow hue showed no significant difference, with values ranging from 36.68% (P1) to 38.43% (P2). Overall, supplementation with 8 g of seaweed meal effectively enhanced the visual red hue of goldfish.